Prescriptivism, nation, and style: The role of nonclassical elements in the stylistic stratification of Modern Hebrew. (22nd December 2016) - Mor, Uri
Abstract : Modern Hebrew (MH) presents an interesting case of a national language whose crystallisation involved not only intensive planning, but also unplanned processes of stratification, which has resulted in a continuous reevaluation and reallocation of existing features. The role of nonclassical inherited elements in this progression is revealing, as they emblematise popular 'authentic' usage on the one hand and diasporic (i.e. nonnative) premodern being on the other, thus exposing the tension between standard and nonstandard language. This study examines the stylistic status of two such elements, be'im 'if' and bixde 'for', 'in order', in two major phases in the short history of MH, in order to characterise the prescriptive discourse of MH and its national undertones.